Modeling computer system states on the structural level in the form of finite state machine - Krivoulya, G. F.; Laptev, M. (ХНУРЭ, 2007)
The construction of diagnostic model of computer system states in the form of finite state machine is considered in the article. The advantage of the model consists in the fact to determine the transitions from one state of the computer system to diagnostic state having the number of input signals.
Keywords: diagnostic model; maintainability; durability; failure; correct state; faulty state; operable state